REPRESENTATION OF JAPANESE CULTURE IN ERAI TOKORO NI TOTSUIDE SHIMATTA BY MAKIMURA KIMIKO - Tia Ristiawati; Yuniarsih; Dwi Astuti Retno Lestari (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2021)
Erai Tokoro Ni Totsuide Shimatta! (ETNTS) by Makimura Kimiko (2006) is one of the Japanese literary works that depicts Japanese culture. This novel tells the story of a character named Makimura Kimiko, a freelance journalist. She recently married a man whose family still followed traditional customs. It is the traditional habits that are very interesting to study. In the current digital era, traditional habits that are rarely found in Japanese society have appeared in this novel. The purpose of this research is to examine cultural representations through traditional habits that appear in this drama through a literary anthropological approach and use John Fiske's semiotic theory.The object of this research material is the novel Erai Tokoro Ni Totsuide Shimatta! (ETNTS) by Makimura Kimiko (2006). The formal object in this study is a representation of Japanese culture.